Long Term Use of Leflunomide as a Cause of Severe Diarrhea? - Zafer Günendi,; Esin Benli,; Feride Göğüş,; Fatma Atalay, (Archives of Rheumatology, 2010)
Leflunomide is a recently developed disease modifying antirheumatic drug that may cause acute diarrhea as an adverse effect. This adverse effect is usually mild and develops during the first few weeks of treatment. In this report, we present a case of rheumatoid arthritis patient with severe diarrhea treated with leflunomide for an extended period of time. (Turk J Rheumatol 2010; 25: 41-3)